Horizontal head-shaking test: pathophysiological mechanisms and clinical interpretation - Marcelli, Vincenzo; Giannoni, Beatrice; Volpe, Giampiero; Cavaliere, Michele; Marcelli, Edoardo; Faralli, Mario; Fetoni, Anna Rita; Pettorossi, Vito E. (Frontiers in Neurology, 2026)
The horizontal head-shaking test (HST) is a simple, rapid, and non-invasive bedside maneuver that provides valuable insights into both peripheral and central vestibular function. Originally described in the late 19th century and standardized in the 1970s, the HST predominantly stimulates the lateral semicircular canals (LSCs) at high frequencies. Its diagnostic power lies in revealing dynamic asymmetries of the angular vestibulo-ocular reflex (aVOR) and uncovering central abnormalities involving the brainstem and, above all, cerebellum. The pathophysiological basis of post-head-shaking nystagmus (post-HSN) derives from Ewald’s second law, which explains the excitatory–inhibitory imbalance between the labyrinths, further processed through the velocity storage mechanism (VSM). The VSM extends and integrates canal signals, aligning them with gravity through the action of the cerebellar nodulus and ventral uvula. Its modulation determines the direction, duration, and morphology of post-HSN, accounting for central features such as perverted or minimal-stimulus responses. The VSM is furthermore crucial for higher-order functions such as motion perception, spatial orientation, and postural stability. Clinically, the HST contributes to discrimination between peripheral lesions—typically producing monophasic or biphasic horizontal post-HSN—and central disorders, which yield vertical or torsional (perverted) responses, or exaggerated responses due to cerebellar disinhibition. Thus, rather than an empirical test, the HST represents a neurophysiologically grounded tool that bridges bedside observation and the vestibular integration. When interpreted within a comprehensive clinical framework, it offers diagnostic, prognostic, and educational value, serving as a window into the physiology and pathology of vestibular–cerebellar networks.